Sustainable development goals in teacher education: comparing syllabi in a Japanese and a Slovenian university - Fiel’ardh, Khalifatulloh; Torkar, Gregor; Rožman, Hana; Fujii, Hiroki (Frontiers in Education, 2023)
In this study, a qualitative content analysis was supplemented with insights from semi-structured interviews, offering a nuanced exploration of the integration of Sustainable Development Goals (SDGs) within the syllabi of the Faculty of Education at Okayama University, Japan (n = 2,079), and the University of Ljubljana, Slovenia (n = 504). Our methodology not only sought to discern the degree of alignment between teacher education programs and the SDGs but also to identify divergences in SDGs emphasis between the two Education for Sustainable Development (ESD)-committed universities. Interview reflections formed a crucial component of our analysis, with respondents acknowledging their pivotal role in actualising the SDGs through teacher education. There was a shared recognition among respondents regarding the imperative of collaborative efforts in fulfilling these global objectives. Their insights illuminated the findings from the syllabi content analysis, which identified a strong focus on Quality Education (SDG 4) in both institutions. However, it also uncovered certain SDGs that were less represented, such as Climate Action (SDG 13), indicating an area for potential improvement. Additionally, disparities were noted in the distribution of SDGs-related content between compulsory and elective courses, hinting at underlying institutional priorities. Conclusively, this research underscores the urgency of bridging identified gaps in SDG coverage, fostering an exchange of effective strategies, and encouraging partnerships across teacher education institutions. By harnessing these collective efforts and insights, teacher education programs can significantly enhance their relevance and efficacy in promoting the SDGs.